(untitled) (Hungarian Journal of Industry and Chemistry, 2011)
This paper shortly describes modern hard machining methods and some of the possibilities of rotational turning. The methods of tangential feed turning are grouped by the numbers of cutting edges, the path of the feed rate and the position of the cutting edge. The important geometrical characteristics of rotational turning are summarized to analyse it for simplification. Finally, based on the results simpler tool geometry was created and some calculations were made for the preparation of an experiment.